The aircraft book the definitive visual history - Hodgson, Nicola; Stone, Chris; Sturgeon, Alison; Summers, David; Ombler, Gary (Dorling Kindersley Limited, 2013)
This title is all about the men, machines, and landmark technology behind the most iconic aircraft from the Supermarine Spitfire to the Concorde. Featuring over 1000 of the greatest military and commercial aircraft in the world, this is an amazing visual guide tracing their evolution over the past 10 decades.